Body Language in the Poetry of Ibn Al-Jayab Al-Farnati (Journal of the College of Languages (JCL), 2017)
Language is a means of communication among the human beings. Every language that distinguish them from others. However, there is language common that is common of all human beings without discrimination and expression of ideas. Perhaps it is more honest that the usual language. The research is divided into a preface which speaks about the meaning of body language. Then we speak about body gestures like the eyes, hand, the tongue the heart reaching up the conclusion in which we found that the body language is one of the terms included in the Holy Quran, which has original roots. But this term is recently common and spread in the present time. Most of those who tackle it were westerners. Sometime it took the role of the spoken language and mostly it is more honest. Each gesture has an independent message that is conveyed to the receiver. The volume of Ibn Al-Jayab includes in its parts many examples of body language.